Contextual advertising in games: Impacts of game context on a player's memory and evaluation of brands in video games - Yoo, Seung-Chul; Eastin, Matthew S. (Journal of marketing communications)
Contextual advertising is growing in digital marketing communication. Previous research on traditional media has shown that the surrounding context affects advertising effectiveness. Similarly, the context in a game may influence a player's processing of brands advertised in that game. To examine the effects of contextual advertising in games, the present article affords two independent experiments investigating how positive and negative game contexts influence players' memories and attitudes with respect to brands advertised via billboards in games. Drawing from literature on the limited capacity model, the authors demonstrate that positive and negative game contexts decrease brand memory since they require a high level of cognitive effort. The authors also find that varying a game context influence the perception of brands advertised in the game via the contextual priming mechanism and that positive contexts generate more positive brand attitudes than negative or neutral contexts. The findings have important implications for consumer researchers and marketers, as they indicate how contexts in games can be utilized to establish brand awareness and increase positive brand perceptions in contextual advertising using games.